Pengendalian Biologi dengan Daya Predasi Berbagai Jenis Ikan terhadap Larva Aedes Aegypti di Wilayah Kerja Puskesmas Tigo Baleh - Mila Sari; Vina Novela (Jurnal Sehat Mandiri, 2020)
Aedes Aegypty mosquito is a vector of dengue in tropical and subtropical regions. At present the eradication of dengue hemorrhagic fever has been done by eradicating mosquitoes, one of which is biological control. Biological control is carried out on the larvae of Aedes using predation power of various larvae. This is done in order to reduce the negative impact of the use of pesticides from chemicals. This control is intended so that fish larvae can prey on larvae in water reservoirs. This study aims to determine the most effective fish to become Aedes Aegypti larvae predators. This type of research uses an experimental method with Post test only design. This research was conducted with two test methods, namely laboratory tests and field tests in the Tigo Baleh Community Health Center. From the results of laboratory tests, there was a significant difference between the eating power of guppies, carp, tilapia, betta fish, betta fish, lead fish, larvae fish, and beunteur fish. The results showed that the most effective predation power was betta fish with a p value of 0,000. Field test found that there was a significant difference (p.Value = 0,000) between the feeding power of betta fish, lead fish, and larvae fish with the most effective predation level was betta fish. So it is necessary to socialize with the community so that people know and practice it directly.